Research Progress on Protein Ingredients and Their Application Challenges in High-protein Baked Products - Feng PANG; Yangchao GAO; Yuchuan LI; Yanqiong LI; Shuhui YU; Haiying WANG; Yuyu ZHANG; He LIU (Shipin gongye ke-ji)
With the improvement of people's consumption level and the pursuit of health and nutrition, high protein bakery products are increasingly favored by consumers. This article provides a comprehensive review of the characteristics and current application status of high-protein ingredients that are commonly used and being explored for use in high-protein baked products. It also summarizes the challenges faced during the application process of these high-protein ingredients and the corresponding solutions. Accordingly, the possible development directions of high protein baking products are pointed out, with a view to providing references and new ideas for the development and industrialization of new high-protein bakery products.